THE LEGAL POSITION OF CREDITORS OUTSIDE THE DEED OF PEACE THAT HAS OBTAINED PERMANENT LEGAL FORCE : CASE STUDY OF PT. XXX - Azet Hutabarat (Universitas Dharma Wacana, 2022)
Law Number 37 of 2004 concerning Bankruptcy and PKPU (Suspension of Debt Repayment Obligations) provides an opportunity to propose reconciliation so that the debtor has the opportunity to settle all receivables responsibly and has a method and process for settlement of settlement and payment properly. But is the purpose of settling all debtor receivables only limited to existing creditors and binding on PKPU institutions? What about the fate of creditors who are outside PKPU and have even obtained legal force through civil decisions? Because the essence of peace as the principle of debt forgiveness (debt forgiveness principle) should also provide legal certainty for all creditors without exception. Has bankruptcy law and civil procedural law accommodated and provided protection for all creditors without exception? This research and writing is an event that actually happened but unfortunately creates the impression that there is a legal conflict and battle between bankruptcy law and civil procedural law, so that the essence of the principle or principle of debt pooling law is in the best law.In this study, the authors conducted research on aspects of normative legal research and sociological or empirical legal research. These two aspects are the reference for research carried out by the author by finding and seeking answers to legal issues raised as a goal to obtain results from the research conducted. Both aspects of this research serve as a reference for obtaining the results obtained as a conclusion as well as input in the form of suggestions from the writings on this legal research.Investigation of the legal principles contained in positive law as data that is juxtaposed with the principles of bankruptcy law should be important to be used in interpreting or interpreting statutory regulations. All parties, both in the context of enforcing bankruptcy law and civil procedural law, really should adhere to and be respected, such as the principle of concursus creditorium, the parity creditorium principle adopted in civil law is in line with the debt collection principle which is so inherent in the principle of bankruptcy law. Alignment of legal principles and applicable legal principles should always be a reference and guide for every party who has an interest in the bankruptcy process. So that there is no longer any dichotomy of applicable law, civil procedural law or bankruptcy law as laws as if they were running separately. If all parties want to adhere to the applicable legal principles, as Satjipto Raharjo stated that legal principles are a legal ratio of legal regulations or as a reason for the birth of legal regulations.